Said Nursi's Concept of God and Nature: A Critique of The Views of Atheism and Naturalism - Zarkasyi, Amal Fathullah; Widodo, Chandra Dwisetyo (RUSYDIAH: Jurnal Pemikiran Islam, 2023)
This research examines Nursi's conceptualization of God and Nature as a critical response to Atheism and Naturalism. In their view, nature is an independent and self-operating system, so God has no place in the mechanism of nature. This view is inseparable from the secularism, materialism, positivism and scientism they uphold. Answering this problem, Said Nursi, an Islamic scholar, tried to respond to the concept of God and Nature that was not in accordance with Islam, even the view actually degraded nature itself as God's creation. This study employs a qualitative approach and utilizes the critical analysis methodology, with the primary source of reference being Risalah Nur. The findings of the article reveal that Atheism and Naturalism have a false understanding of nature and God. In Nursi's view, nature depends on God and does not work alone. Said Nursi has also developed a theological understanding of nature, arguing that the existence of God can be inferred from the birth of the universe. Nursi revealed that the universe is a great book and a marvellous work of God's art, it is like a mirror that reflects the beauty of its Creator. Nursi said that proving God's existence makes more sense than the arguments that reject His existence.